Bacteriological study of uropathogens with correlation of various screening test with culture and their antimicrobial susceptibility - Bawankar, Smita; Enam, Sk. Khairul; Panda, Animesh; Chandi, Dhruba Hari (Asian Journal of Medical Sciences, 2016)
Background: UTI is most distribution of uropathogens amongst the community & hospitalized patients suffering bacterial infection. Aims and Objectives: It affects person throughout their life span. It may be characterized as uncomplicated (occurring without an anatomic or other predisposing reason) or complicated (associated with structural or functional abnormalities of the urinary tract & kidney). A single bacterial species Escherichia coli, causes majority of UTI. Materials and Methods: Total of 426 clinically diagnosed uti cases were subjected to culture & its correlation with various screening tests such as wet film microscopy, TTC & Gram stain & its sensitivity, specificity, positive & negative productive value were determine along with anti microbial susceptibility also virulence factor of E. coli & ESBL production were studied. Results: Present study showing UTI was more common in females 281 (65.96%) as compared to 145 (34.03%) in males. As compare with culture, sensitivity of TTC, wet film microscope were 78.22%, 81.91% & 97.41% respectively. Amongst total 271 culture isolates E. coli were more common, highest resistant was observed to ampicillin (90.78%) followed by amoxyclave (86.64%), cotrimoxazole (82.23%) & carbenicillin (78.94%), whereas highest sensitivity noted against imipenem (100%). Conclusion: It is evident UTI is more common in reproductive females & in case of males in older age. Asian Journal of Medical Sciences Vol. 7(3) 2016 108-114